In Vitro and In Vivo Evaluation of the Toxic Effects of Dodecylguanidine Hydrochloride - Yeon-Mi Lim; Haewon Kim; Seong Kwang Lim; Jean Yoo; Ji-Young Lee; Ig-Chun Eom; Byung-Il Yoon; Pilje Kim; Seung-Do Yu; Ilseob Shim (Toxics, 2020)
The toxicity profiles of the widely used guanidine-based chemicals have not been fully elucidated. Herein, we evaluated the in vitro and in vivo toxicity of eight guanidine-based chemicals, focusing on inhalation toxicity. Among the eight chemicals, dodecylguanidine hydrochloride (DGH) was found to be the most cytotoxic (IC50: 0.39 μg/mL), as determined by the water soluble tetrazolium salts (WST) assay. An acute inhalation study for DGH was conducted using Sprague-Dawley rats at 8.6 ± 0.41, 21.3 ± 0.83, 68.0 ± 3.46 mg/m3 for low, middle, and high exposure groups, respectively. The levels of lactate dehydrogenase, polymorphonuclear leukocytes, and cytokines (MIP-2, TGF-β1, IL-1β, TNF-α, and IL-6) in the bronchoalveolar lavage fluid increased in a concentration-dependent manner. Histopathological examination revealed acute inflammation with necrosis in the nasal cavity and inflammation around terminal bronchioles and alveolar ducts in the lungs after DGH inhalation. The LC50 of DGH in rats after exposure for 4 h was estimated to be >68 mg/m3. Results from the inhalation studies showed that DGH was more toxic in male rats than in female rats. Overall, DGH was found to be the most cytotoxic chemical among guanidine-based chemicals. Exposure to aerosols of DGH could induce harmful pulmonary effects on human health.